Human Resources Competence, Accounting Information Systems and Quality of Financial Reports in Cooperatives in East Lombok Regency - Iska, Sulis Hidayatul; Lenap, Indria Puspitasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this investigation is to examine and evaluate the effect of skill and accounting procedures on the content of financial statements. A survey method was used to distribute questionnaires to cooperatives in East Lombok Regency. This research uses primary data through a survey method to gather primary data. The selection of the sample was carried out through a specific sampling method, and 80 individuals completed the questionnaire. The data was processed with the SmartPls 4.0 software after being processed. The findings reveal that the proficiency of personnel and accounting information systems affects the content of financial statements. Furthermore, by utilizing accounting information system technology, it can provide excellence and accuracy in the process of preparing financial reports for cooperatives.